1998
DOI: 10.1007/bf01417674
|View full text |Cite
|
Sign up to set email alerts
|

Specification and evaluation of level of detail selection criteria

Abstract: Level of detail (LOD) is a technique where geometric objects are represented at a number of resolutions, allowing the workload of the system to be modulated on-line. There are numerous schemes for implementing LOD, using selection criteria based upon an object's distance, size, velocity, or eccentricity. However, little is known about how to specify optimally when a particular LOD should be selected so that the user is not aware of any visual change, or to what extent any particular LOD scheme can improve an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…Geometric detail elision in the periphery has been proposed by many researchers [Cheng 2003;Luebke et al 2000;Murphy and Duchowski 2001;Ohshima et al 1996;Reddy 1998;Reddy 2001;Weaver 2007]. We use a simple technique for geometric LOD management described in Section 6, but another could be substituted.…”
Section: Foveated Geometric Detail Elisionmentioning
confidence: 98%
“…Geometric detail elision in the periphery has been proposed by many researchers [Cheng 2003;Luebke et al 2000;Murphy and Duchowski 2001;Ohshima et al 1996;Reddy 1998;Reddy 2001;Weaver 2007]. We use a simple technique for geometric LOD management described in Section 6, but another could be substituted.…”
Section: Foveated Geometric Detail Elisionmentioning
confidence: 98%
“…Thus, in order to save scene-rendering time, which can otherwise be quite extensive, multi-resolutional VR displays are commonly used (for a recent review, see Luebke et al, 2002), and these are most often head-contingent (e.g., Ohshima, Yamamoto, & Tamura, 1996;Reddy, 1997;Watson et al, 1997). Reddy (1997, p. 181) has, in fact, argued that head tracking is often all that is needed to provide substantial savings in multi-resolutional VR displays, and he showed that taking account of retinal eccentricity created very little savings in at least two different VR applications (Reddy, 1997;Reddy, 1998). However, the applications he used had rather low maximum resolutions (e.g., 4.8-12.5 cycles/degree, or 9.6-25 pixels/degree).…”
Section: Virtual Realitymentioning
confidence: 99%
“…There has also been major work on gaze-contingent systems [Duchowski 2002] and peripherally degraded displays [Reddy 1998;Watson et al 1997]. There has been much previous research into saliency [Itti et al 1998;Yee et al 2001].…”
Section: Introductionmentioning
confidence: 99%